Salon 1956 :. (Antwerpen : Kunst van Heden, 1956)
Jespers, Oscar ; Bertrand, Gaston ; Bonnet, Anne ; Creado, Emiel ; De Maeyer, Lod. ; D'Haese, Roel ; Devos, Pierre ; Dudant, Roger ; Godderis, Jack ; Guiette, René ; Hendrickx, Jos. ; Joostens, Paul ; Macken, Mark ; Magritte, René ; Mara, Pol ; Marstboom, Antoon ; Paerels, Willem ; Scauflaire, Edgar ; Tytgat, Edgard ; Vanderlick, Armand ; Vinck, Jozef ; Wolvens, Henri Victor
Salon 1956, Stedelijke Feestzaal, Meir, Antwerpen, 6 - 28 october 1956
boek